Community participation and empowerment approaches to Aedes mosquito management in high-income countries: a scoping review. (10th July 2020) - Allen, Tammy; Crouch, Alan; Topp, Stephanie M
Abstract: High-income countries (HICs) in sub-tropical and tropical regions are at an increasing risk of Aedes mosquito-borne disease (MBD) outbreaks such as dengue fever. As the Aedes mosquito predominately lives and breeds in and around people's homes, community participation in MBD management is an important part of preventing MBD outbreaks. Historically, government-led strategies have dominated community participation efforts as opposed to strategies co-designed or led by the community. A scoping review was conducted to describe the community participation and empowering approaches used in Aedes mosquito management specifically in HICs, and to identify any reported outcomes of these methods. A systematic search of peer-reviewed literature using electronic databases Medline (OVID), Web of Science, Scopus and ProQuest—Science and Technology as well as grey literature, found 19 studies that matched the review criteria. The review findings highlight a lack of empirical evidence to inform participatory and empowering approaches to mosquito management in HICs. Moreover, the rationale for using predominantly government-led approaches is not clear. Further research is required to better understand best approaches and barriers to employing empowering approaches in mosquito management in HICs.